Isoflavones and PPAR Signaling: A Critical Target in Cardiovascular, Metastatic, and Metabolic Disease. (26th December 2010) - Patel, Rakesh P.; Barnes, Stephen
Abstract : Isoflavone intake through foods and dietary supplements has both health advocates and critics. The latter come from a concern about the estrogenic effects of isoflavones in certain species. However, careful removal of isoflavones and other estrogens from the diet of rodents leads to the metabolic syndrome. These results suggest that isoflavones have other mechanisms of action, potentially those involving regulation of fatty acid metabolism via the nuclear receptors PPAR α and PPAR γ . The goal of this paper was to examine the evidence for isoflavone/PPAR signaling and to identify diseases in which such signaling would have an important impact. It is therefore of note that investigators using a chemical structure approach to discover PPAR ligands identified isoflavones as the best structures in the library of compounds that they tested. Future studies will involve careful identification of the underlying mechanisms whereby isoflavones have their action via PPAR signaling.